2020
DOI: 10.1177/1073191120911095
|View full text |Cite
|
Sign up to set email alerts
|

Burnout–Depression Overlap: Exploratory Structural Equation Modeling Bifactor Analysis and Network Analysis

Abstract: Burnout has been viewed as a work-induced condition combining exhaustion, cynicism, and professional inefficacy. Using correlational analyses, an exploratory structural equation modeling bifactor analysis, structural regression analyses, and a network analysis, we examined the claim that burnout should not be mistaken for a depressive syndrome. The study involved 1,258 educational staff members. Burnout was assessed with the Maslach Burnout Inventory–General Survey and depression with the Patient Health Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 104 publications
6
51
0
Order By: Relevance
“…Third, we conducted our literature review up to 2018. Although no new definition of burnout has been introduced in the scientific literature since then, several factor-analytic studies have recently concluded that Harmonized burnout definition, finally burnout-and most notably, exhaustion-was reflective of a depressive condition (47,48). Because our temporal limit was 2018, we did not incorporate these findings in our analyses.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Third, we conducted our literature review up to 2018. Although no new definition of burnout has been introduced in the scientific literature since then, several factor-analytic studies have recently concluded that Harmonized burnout definition, finally burnout-and most notably, exhaustion-was reflective of a depressive condition (47,48). Because our temporal limit was 2018, we did not incorporate these findings in our analyses.…”
Section: Study Limitationsmentioning
confidence: 99%
“…To better address this issue, the CAT-Q and other putative camouflaging scales should be subjected to quantitative semantic analysis (Rosenbusch, Wanders, & Pitt, 2020) to determine whether they are indeed substantially similar to existing measures of social anxiety. In addition, future studies of discriminant validity should be conducted using multimeasure latent variable models, which can test hypotheses about whether two sets of items seem to measure one single overarching construct (e.g., testing the distinctiveness of burnout and depression; Verkuilen, Bianchi, Schonfeld, & Laurent, 2020).…”
Section: Self-report Measures Of Camouflagingmentioning
confidence: 99%
“…Kottwitz et al (2013) suggests that illegitimate tasks predict cortisol levels in participants who rated their health comparatively low (b = 1.43, p < 0.01). Verkuilen et al (2020) report that unreasonable tasks and unnecessary tasks are positively correlated with burnout (r = 0.4 and 0.36) and depression (r = 0.42 and 0.37) and are predictors of general distress. Pereira finds that illegitimate tasks are negatively related to sleep quality; specifically, they are positively related to sleep fragmentation and sleep latency (Pereira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%